2002
DOI: 10.1007/s00449-002-0280-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced pilot-scale fed-batch L-phenylalanine production with recombinant Escherichia coli by fully integrated reactive extraction

Abstract: A fully integrated process for the microbial production and recovery of the aromatic amino acid L-phenylalanine is presented. Using a recombinant L-tyrosine (L-Tyr) auxotrophic Escherichia coli production strain, a fed-batch fermentation process was developed in a 20-l-scale bioreactor. Concentrations of glucose and L-Tyr were closed-loop-controlled in a fed-batch process. After achieving final L-phenylalanine (L-Phe) titres >30 g/l the process strategy was scaled up to 300-l pilot scale. In technical scale fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 65 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…When necessary, the following concentrations of antibiotics were added to the medium to maintain plasmids: 100 μg/mL ampicillin (Amp) and 40 μg/mL kanamycin (Kan). Flask cultivation for the production of l -phenylalanine was performed using modified fermentation medium previously [ 51 53 ]. The composition of the fermentation medium is: 20 g/L glucose, 3 g/L KH 2 PO 4 , 5 g/L (NH 4 ) 2 SO 4 , 1 g/L NaCl, 1.5 g/L sodium citrate, 0.015 g/L CaCl 2 ∙2H 2 O, 3 g/L MgSO 4 ∙7H 2 O, 0.01125 g/L FeSO 4 ∙7H 2 O, 0.075 g/L Thiamine-HCl, 0.3 g/L l -tyrosine (L-Tyr), 0.03 g/L l -tryptophan (L-Trp), 3 g/L yeast extract, and 1.5 mL/L trace element solution (TES) at pH 6.8.…”
Section: Methodsmentioning
confidence: 99%
“…When necessary, the following concentrations of antibiotics were added to the medium to maintain plasmids: 100 μg/mL ampicillin (Amp) and 40 μg/mL kanamycin (Kan). Flask cultivation for the production of l -phenylalanine was performed using modified fermentation medium previously [ 51 53 ]. The composition of the fermentation medium is: 20 g/L glucose, 3 g/L KH 2 PO 4 , 5 g/L (NH 4 ) 2 SO 4 , 1 g/L NaCl, 1.5 g/L sodium citrate, 0.015 g/L CaCl 2 ∙2H 2 O, 3 g/L MgSO 4 ∙7H 2 O, 0.01125 g/L FeSO 4 ∙7H 2 O, 0.075 g/L Thiamine-HCl, 0.3 g/L l -tyrosine (L-Tyr), 0.03 g/L l -tryptophan (L-Trp), 3 g/L yeast extract, and 1.5 mL/L trace element solution (TES) at pH 6.8.…”
Section: Methodsmentioning
confidence: 99%
“…The production of L-phenylalanine by various recombinant E. coli strains using glucose or sucrose as carbon sources has been discussed extensively in the literature [2,8,9,14,19,26,31,32], but reports on the use of glycerol for this fermentation are nonexistent.…”
Section: Introductionmentioning
confidence: 99%
“…In development of industrial process, E. coli gives the advantages of high growth and production rates combined with high yields by using simple media which are suitable for product recovery efficiently (Gerigk et al, 2002). Hence, using recombinant E. coli strains is a great deal on the L-Phe process development and many research works have been patented (Kim et al, 1994, Lim et al, 1995, Sprenger et al, 1998.…”
Section: L-phenylalanine Productionmentioning
confidence: 99%
“…This enzyme is also sensitive to feedback inhibition mediated by allosteric binding of L-Phe (Pittard, 1996, Zhang et al, 1998. Gerigk and coworkers used recombinant E. coli carrying feedback-resistant pheA (pheA fbr ) and feedback-resistant aroF (aroF fbr ) to synthesize L-Phe in 20 L bioreactor and achieved more than 30 g/L of L-Phe (Gerigk et al, 2002). It also has been reported that the construction of genetically modified E. coli strain with pheA fbr and aroF fbr , with L-Phe titer of 50 g/L was achieved after 36 h (Backman et al, 1990).…”
Section: Metabolic Engineering For Biosynthesis Of L-phenylalanine In...mentioning
confidence: 99%
See 1 more Smart Citation